Yoga posture recognition by detecting human joint points in real time using microsoft kinect - Islam, Muhammad Usama; Mahmud, Hasan; Ashraf, Faisal Bin; Hossain, Iqbal; Hasan, Md. Kamrul (2017 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2017)
Musculoskeletal disorder is increasing in humans due to accidents or aging which is a great concern for future world. Physical exercises can reduce this disorder. Yoga is a great medium of physical exercise. For doing yoga a trainer is important who can monitor the perfectness of different yoga poses. In this paper, we have proposed a system which can monitor human body parts movement and monitor the accuracy of different yoga poses which aids the user to practice yoga. We have used Microsoft Kinect to detect different joint points of human body in real time and from those joint points we calculate various angles to measure the accuracy of a certain yoga poses for a user. Our proposed system can successfully recognize different yoga poses in real time.